Randomised controlled trial of an education and support package for stroke patients and their carers. Issue 5 (8th May 2013) - Eames, Sally; Hoffmann, Tammy; Worrall, Linda; Read, Stephen; Wong, Andrew
Abstract : Objective: Tailoring stroke information and providing reinforcement opportunities are two strategies proposed to enhance the effectiveness of education. This study aimed to evaluate the effects of an education package which utilised both strategies on the knowledge, health and psychosocial outcomes of stroke patients and carers. Design: Multisite, randomised trial comparing usual care with an education and support package. Setting: Two acute stroke units. Participants: Patients and their carers (N=138) were randomised (control n=67, intervention n=71) of which data for 119 participants (control n=59, intervention n=60) were analysed. Intervention: The package consisted of a computer-generated, tailored written information booklet and verbal reinforcement provided prior to, and for 3 months following, discharge. Outcome measures: Outcome measures were administered prior to hospital discharge and at 3-month follow-up by blinded assessors. The primary outcome was stroke knowledge (score range: 0–25). Secondary outcomes were: self-efficacy (1–10), anxiety and depression (0–21), ratings of importance of information (1–10), feelings of being informed (1–10), satisfaction with information (1–10), caregiver burden (carers) (0–13) and quality of life (patients) (1–5). Results: Intervention group participants reported better: self-efficacy for accessing stroke information (adjusted mean difference (MD) of 1.0, 95% CI 0.3 to 1.7, p=0.004); feeling informed (MD 0.9, 95% CI 0.2 to 1.6, p=0.008); and satisfaction with medical (MD 2.0, 95% CI 1.1 to 2.8, p<0.001); practical (MD 1.1, 95% CI 0.3 to 1.9, p=0.008), services and benefits (MD 0.9, 95% CI 0.1 to 1.8, p=0.036) and secondary prevention information (MD 1.7, 95% CI 0.9 to 2.5, p<0.001). There was no significant effect on other outcomes. Conclusions: Intervention group participants had improved self-efficacy for accessing stroke information and satisfaction with information, but other outcomes were not significantly affected. Evaluation of a more intensive intervention in a trial with a larger sample size is required to establish the value of an educational intervention that uses tailoring and reinforcement strategies. ACTRN12608000469314